Melinjo fruit outer skin peeler prototype design using grate roller based-on auto reverse movement control - Yunidar Yunidar; Riska Sufina; Alfa Tirta Mufti; Melinda Melinda; Iskandar Hasanuddin (Jurnal Polimesin, 2023)
Cracker snacks made from melinjo fruit are often found in the Pidie Regency area, Aceh. However, processing melinjo seeds into crackers is still manual and takes a long time. In this research, a melinjo peeling machine will be designed to speed up the production process of melinjo crackers. This peeler uses two different electricity sources so it can work in two conditions, namely the PLN electricity supply is on or off. The research method was carried out by collecting data from device testing results and field observations as well as comparing test results with previous research. The movement of the motor is controlled using Time Delay which gives a command to activate the relay and then turns on the 12 V DC motor. The motor rotates clockwise and anti-clockwise continuously (auto reverse) according to the direction of positive and negative potential which is controlled by the relay and Time Delay. The success rate of peeling the outer skin of melinjo seeds using the proposed tool is divided into three types based on differences in seed skin color. The percentage of success for red, orange, and yellowish green melinjo was 68.67%, 51.52% and 25.61% respectively. Thus, in this study, it can be concluded that the most efficient success rate is for red melinjo